2020
DOI: 10.1111/odi.13258
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of calprotectin in the saliva of patients with geographic tongue

Abstract: Objective We investigated whether patients with geographic tongue have increased salivary levels of calprotectin and whether there is a correlation between the salivary levels of calprotectin and interleukin 8 (IL‐8), which is another marker of inflammation. Methods Twenty‐three patients diagnosed with geographic tongue and 32 control subjects without oral mucosal lesions were included in the study. The patients with geographic tongue were classified based on clinical appearance and number of oral lesions. ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, calprotectin level in saliva was significantly related to two oral hypofunctional tests of oral moisture and masticatory function in adjusting for covariate (age, sex and periodontal stage). Previous studies on the association between these biomarkers and oral or systemic diseases have reported that salivary calprotectin levels are elevated in patients with geographical tongue [ 44 ] or Shögren’s syndrome [ 25 ], suggesting a weakly correlation between salivary calprotectin and oral moisture via decreased salivation. Furthermore, the association between fecal calprotectin levels and Alzheimer's disease [ 23 ] and reports of calprotectin secretion from skeletal muscle tissue during exercise [ 45 ] suggest that calprotectin may be involved in movement function of the tongue and lip through its involvement in these muscles and neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, calprotectin level in saliva was significantly related to two oral hypofunctional tests of oral moisture and masticatory function in adjusting for covariate (age, sex and periodontal stage). Previous studies on the association between these biomarkers and oral or systemic diseases have reported that salivary calprotectin levels are elevated in patients with geographical tongue [ 44 ] or Shögren’s syndrome [ 25 ], suggesting a weakly correlation between salivary calprotectin and oral moisture via decreased salivation. Furthermore, the association between fecal calprotectin levels and Alzheimer's disease [ 23 ] and reports of calprotectin secretion from skeletal muscle tissue during exercise [ 45 ] suggest that calprotectin may be involved in movement function of the tongue and lip through its involvement in these muscles and neurotransmission.…”
Section: Discussionmentioning
confidence: 99%